Modelling of Secondary Flow Vortex Structures, Hydrodynamic Instability and Associated Heat Transfer in Fluid Flow Through Curved Ducts - Chandratilleke, Tilak; Nadim, Nima; Narayanaswamy, Ramesh (Indian Institute of Technology Madras, 2011)
This paper presents a numerical study that examines the secondary flow and thermal behaviour in curved rectangular ducts. For developing laminar flow through these ducts, a novel 3-dimensional model based on vortex structures is formulated and a parametric influence is examined using the contours of helicity for a range of fluid flow rates, duct aspect ratios and wall heat fluxes. The flow and geometrical conditions leading to hydrodynamic instability are identified. Results are validated against experimental data. The study presents a novel method for determining the onset of hydrodynamic instability.